Respiratory Induced Modulation in f-Wave Characteristics During Atrial Fibrillation - Abdollahpur, Mostafa; Holmqvist, Fredrik; Platonov, Pyotr G.; Sandberg, Frida (Frontiers in Physiology, 2021)
The autonomic nervous system (ANS) is an important factor in cardiac arrhythmia, andinformation about ANS activity during atrial fibrillation (AF) may contribute to personalizedtreatment. In this study we aim to quantify respiratory modulation in the f-wave frequency trendfrom resting ECG. First, an f-wave signal is extracted from the ECG by QRST cancellation. Second,an f-wave model is fitted to the f-wave signal to obtain a high resolution f-wave frequency trend andan index for signal quality control (S). Third, respiratory modulation in the f-wave frequency trendis extracted by applying a narrow band-pass filter. The center frequency of the band-pass filteris determined by the respiration rate. Respiration rate is estimated from a surrogate respirationsignal, obtained from the ECG using homomorphic filtering. Peak conditioned spectral averaging,where spectra of sufficient quality from different leads are averaged, is employed to obtain arobust estimate of the respiration rate. The envelope of the filtered f-wave frequency trend is usedto quantify the magnitude of respiratory induced f-wave frequency modulation. The proposedmethodology is evaluated using simulated f-wave signals obtained using a sinusoidal harmonicmodel. Results from simulated signals show that the magnitude of the respiratory modulationis accurately estimated, quantified by an error below 0.01 Hz, if the signal quality is sufficient(S>0.5). The proposed method was applied to analyze ECG data from eight pacemaker patientswith permanent AF recorded at baseline, during controlled respiration, and during controlledrespiration after injection of atropine, respectively. The magnitude of the respiratory induce f-wavefrequency modulation was0.15±0.01Hz,0.18±0.02Hz, and0.17±0.03Hzduring baseline,controlled respiration, and post-atropine, respectively. Our results suggest that parasympatheticregulation affects the magnitude of respiratory induced f-wave frequency modulation